EFFORTS TO IMPROVE THE ABILITY OF MATHEMATICAL CONNECTION OF CLASS VIII A MTs AL-HIKMAH 02 TALEGONG STUDENTS ON CIRCLE MATERIALS THROUGH PROBLEM-BASED LEARNING APPROACH - hadin hadin hadin ((JIML) JOURNAL OF INNOVATIVE MATHEMATICS LEARNING, 2019)
This article was made to describe the results of research in MTS AL-Hikmah II Talegong, Garut Regency with 25 students with the aim of improving the indicator of mathematical connection ability, which is reviewed from each cycle, whether from each cycle there is an increase or decrease, on the indicator which students feel difficulties what kind of student performance can lead to low connections in the field. The method used in this study is a descriptive method with a qualitative approach. The research phase consists of planning, implementing class actions, observation and evaluation, and reflection. The results of the study were obtained: 1) in the first cycle the achievement of students' mathematical connection skills was only 16.88%, 2) in the second cycle the achievement of mathematical connection skills increased to 54%, 3) while in the third cycle the average mathematical connection ability increased to 69.75%. Based on the results of the study it can be concluded that class action research to measure indicators of mathematical connection ability has improved better and achieved completeness in cycle three.